2010
DOI: 10.1097/qai.0b013e3181d01d31
|View full text |Cite
|
Sign up to set email alerts
|

Never in Care: Characteristics of HIV-Infected Crack Cocaine Users in 2 US Cities Who Have Never Been to Outpatient HIV Care

Abstract: Background There are very limited data available of the correlates of HIV-infected crack users who have never been to HIV care. Methods Interviews were conducted at bedside with HIV-infected crack cocaine users who were recruited from the inpatient wards at Jackson Memorial Hospital in Miami, FL and Grady Memorial Hospital in Atlanta, GA between August 2006 and July 2009. Participants were asked about their socio-demographic characteristics, drug use, drug/alcohol treatment history, use of HIV care, perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Regarding HIV, it is recommended that users be referred to testing and follow-up facilities and undergo constant monitoring of their adherence to antiretroviral treatment and of their motivation to care for their health and body. 2 With the exception of a positive correlation with safe sexual behavior (condom use), we were unable to identify other factors associated with stability of abstinence trajectories. Notwithstanding, the composition of a group of long-abstinent subjects (group 1) indicated the rupture of skepticism with respect to the impossibility of overcoming crack cocaine addiction and sustaining abstinence for an extended period.…”
Section: Discussionmentioning
confidence: 76%
“…Regarding HIV, it is recommended that users be referred to testing and follow-up facilities and undergo constant monitoring of their adherence to antiretroviral treatment and of their motivation to care for their health and body. 2 With the exception of a positive correlation with safe sexual behavior (condom use), we were unable to identify other factors associated with stability of abstinence trajectories. Notwithstanding, the composition of a group of long-abstinent subjects (group 1) indicated the rupture of skepticism with respect to the impossibility of overcoming crack cocaine addiction and sustaining abstinence for an extended period.…”
Section: Discussionmentioning
confidence: 76%
“…The CDC's HIV Prevention Strategic Plan has promoted the strengthening of linkages between diagnosis and care since 2001 41 and funded the Never in Care Pilot Project 24 and ARTAS studies to address this issue. Our study, along with the study by Bell and colleagues, 19 suggests that improvements in posttest linkages to care remain an area of needed improvement. Interestingly, we found very limited evidence of differences between study groups by testing location, which is different from other studies.…”
Section: Discussionmentioning
confidence: 79%
“…The absence of direct linkages between the HIV diagnosis and care initiation has been documented in just a few other studies. 9,11,19 Most recently, Bell et al 19 found that among a sample of hospitalized, HIVpositive crack cocaine users 40% did not report being helped into care since their HIV diagnosis, and these patients were significantly less likely to have ever been in HIV care than those who reported help getting into care. The CDC's HIV Prevention Strategic Plan has promoted the strengthening of linkages between diagnosis and care since 2001 41 and funded the Never in Care Pilot Project 24 and ARTAS studies to address this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on these increasingly popular nonpharmacologic medical interventions in PLWH remains limited. Furthermore, compared with PLWH who are not substance users, the subpopulation of PLWH who use crack cocaine is typically more socioeconomically unstable and has a greater tendency to be unemployed, to be homeless, 40 and to have legal problems and stints in detention. As a result this group is more difficult to follow.…”
mentioning
confidence: 99%